Injury in ice hockey players - Jozef Kováč (Slovak Journal of Sport Science, 2021)
Ice hockey is a popular sport that brings the risk of various injuries. With the injuries in ice hockey, various pathophysiological mechanisms play a role. The highest rate of injuries occurs in connection to the collision of players and hard objects in the rink or physical contact with other players. A proper physical and clinical examination of a patient plays a crucial role in diagnostics. Various biomechanical factors are applied in ice hockey injuries. Conservative management is one of the various optional therapies. Rehabilitation is a significant part of ice hockey-related injury treatment.